Processing difficulties and biochemical barriers in camel milk fermentation - Ali, Sifatun Nesa; Ayyash, Mutamed; Kamal-Eldin, Afaf (Frontiers in Microbiology, 2026)
Camel milk (CM) is recognized for its high nutritional enrichment, and the distinction from bovine milk mainly because of its unique protein composition, proteolytic products, and anti-microbial compounds. These unique chemical properties have positive effects on the nutritional value but negative impact on the sensory attributes and consumer acceptability of fermented CM. This review summarizes the current state of knowledge on CM fermentation, emphasizing the influence of milk composition on gel and microstructure formation, texture, and overall quality of the products. While the richness of fermented CM in bioactive peptides enhances its nutritional and therapeutic values, major challenges are associated with their thin consistency and weak gel structure. Various strategies to overcome these challenges and develop unique functional fermented CM products are discussed, including the use of alternative starter cultures (e.g., Lactobacillus helveticus, Lb. casei, and Lactiplantibacillus plantarum), stabilizing additives hydrocolloids or proteins, as well as optimized heat treatments, high-pressure processing and other emerging technologies. Despite several processing and formulation procedures, no particular approach has yet offered a comprehensive solution for achieving firm and stable camel yogurt. Therefore, it is important to accept fermented CM products as being different and develop means to improve their sensory quality and consumer acceptance. Overall, this review underscores the necessity for ongoing research to optimize the quality and commercial viability of fermented CM.